Brand Communication Ecosystem and Purchase Intention: The Mediating Role of Halal Brand in Islamic Consumer Markets - Rusdiyanto; Budi Santoso; Riyanto Setiawan Suharsono; Nursaid; Zainudin bin Hassan (IQTISHODUNA: Jurnal Ekonomi Islam, 2026)
This study aims to examine the effects of firm-created communication and user-generated communication on purchase intention through halal brand among halal product consumers in East Java. A quantitative survey design was employed in this research. The population consisted of halal product consumers in East Java Province, and purposive sampling was applied based on halal consumption experience criteria. A total of 500 eligible respondents were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings reveal that firm-created communication and user-generated communication have positive and significant effects on halal brand and purchase intention. Halal brand also positively affects purchase intention and mediates the effects of both communication variables on purchase intention. Practically, these findings highlight the importance of transparent and credible halal communication strategies and digital consumer engagement in strengthening halal brand perception and enhancing consumer purchase intention. Theoretically, this study extends the Theory of Planned Behavior by integrating the perspective of halal consumption behavior, positioning halal brand as a religious trust mechanism in shaping purchase intention. The novelty of this study lies in developing an integrated model that simultaneously examines firm and consumer communication effects on purchase intention through halal brand within the Islamic economics context.